Challenging (-Hindering) Employment and Employee Health - Haines III, Victor; Ricardeau Registre, Jean; Guerrero, Sylvie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2022)
SummaryResearch has struggled with the task of distinguishing high from low-quality employment. Making the distinction between challenging and hindering job demands in a context of social exchange, our study develops a generalizable heuristic for employment quality research. Latent class analysis with mixture modelling was applied to a sample of 2,143 adults from a diversity of occupations. A two-factor model provided substantial support for the distinction between challenging and hindering employment. Challenging employment was characterized by hard and emotionally demanding work and by provision of greater resources. Hindering employment involved several hindering demands and fewer resources. As predicted, challenging employment was associated with better self-reported general health and less psychological distress. The positive associations between higher education levels and longer work experience and challenging employment also supported the challenging/hindering heuristic.AbstractResearch has struggled with the task of distinguishing high from low-quality employment. Making the distinction between challenging and hindering job demands in a context of social exchange, our study develops a generalizable heuristic for employment quality research. Latent class analysis with mixture modelling was applied to a sample of 2,143 adults from a diversity of occupations. A two-factor model provided substantial support for the distinction between challenging and hindering employment. Challenging employment was characterized by hard and emotionally demanding work and by provision of greater resources. Hindering employment involved several hindering demands and fewer resources. As predicted, challenging employment was associated with better self-reported general health and less psychological distress. The positive associations between higher education levels and longer work experience and challenging employment also supported the challenging/hindering heuristic.